Precision of NPK Fertilizer for Swampy Rice Based on In Situ Soil Nutrient Analysis in South Sumatra, Indonesia - Poppy Khairunnisa; Dedik Budianta; Adipati Napoleon (Journal of Smart Agriculture and Environmental Technology, 2025)
Precision of fertilizer is an approach that directs the use of fertilizers in a rational, efficient, and targeted manner, so that plants obtain sufficient nutrients for optimal growth without causing waste or negative impacts on the environment. This study aims to determining the doses of N, P, and K fertilizers that are appropriate for  swampland by implementing a site-specific fertilization approach using in situ soil analysis. This research used a systematic method with 15 sample points, Soil sampling was conducted using a composite method and soil drilling with soil depth of 0-30 cm. The parameters observed were N-total, P-available, k-exchangeable, soil pH, and C-organic. The study found that the soil in Ulak Bedil Village exhibited highly acidic conditions (pH 3.80–4.47), with varied nutrient availability. Based on soil N, P, and K analysis and rice plant nutrient requirements, site-specific fertilizer recommendations were determined. The recommended fertilizer doses are 91.30 kg ha−1 for urea, 31.03 kg ha−1 for SP-36, and 109.65 kg ha−1 for KCl. This research provides a practical guideline for the application of site-specific fertilization to rice cultivation in swampland, in order to increase yields while reducing negative impacts on the environment.